English Public Speaking Anxiety: Intercultural Communicative Competence Perspective - Dhira Nada Azahra; Muhammad Ghiyats An Nabhan; Hudiya Rusyda Nurzakkiyah Ismail; Ratna Andhika Mahaputri; Yuna Mumpuni Rahayu (Publikasi Indonesia, 2025)
Public speaking is one of the common issues in the EFL context but is not limited to the student teachers in Indonesia. To better understand this matter, 15 in-depth interviews and questionnaires were carried out among student teachers in a private university in Indonesia. The research integrates Byram’s model of Intercultural Communicative Competence (ICC) to examine how knowledge, attitude, and skills of interpreting and navigating aspects of cultures influence English public speaking anxiety among them. The findings show that linguistic insecurities, fear of negative evaluation, and psychological stress are the predominant issues impacting students’ public speaking skills at the university level. In this sense, the study reveals that students’ intercultural communicative competence (ICC) plays a significant role in moderating their anxiety, where higher ICC correlates with lower anxiety levels. Psycholinguistic factors such as negative self-perception, lack of confidence, and concerns over cultural miscommunication also significantly contribute to the fear of English public speaking. The findings implicate that enhancing communication education with integrated ICC components and fostering supportive, culturally sensitive learning environments could mitigate this anxiety, potentially improving students’ English public speaking performance. Further research engaging a wider population is necessary for policy formulation, which might facilitate the culture learning in public speaking among students of all educational levels.